Pengaruh Senam Zumba terhadap Penurunan Kadar Gula Darah Sewaktu pada Penderita DM Tipe 2 di Puskesmas Kedungmundu Kota Semarang - Laurensia Juliani; Suharyo Suharyo (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Diabetes mellitus is chronic disease caused by the pancreas is unable to produce enough insulin and the body can not effectively use the insulin. International Diabetes Federation mentioned that cases of diabetes mellitus in the world, 2012 reached 23.41milion people and will increase to 366 milion people in 2030. Based on data from the city health office Semarang years 2012-2014, cases of type 2 diabetes mellitus in the Kedungmundu primary health center is the highest among all primary health centers in Semarang, as many as 2,147 cases in 2012, 1,713 cases in 2013 and 3,073 cases in 2014. There are four ways to control diabetes, one of them is doing excercise. The exercise, at least 30 minutes, can control blood sugar level. Exercises are recommended for diabetics are aerobic exercises such as jogging, walking, and gymnastic in group. In 2012 zumba became famous and it is gymnastic group that combines elements of aerobic and dance. The purpose of this study was to determine the effect of gymnastic zumba to decrease blood sugar on people with type 2 diabetes mellitus in the Kedungmundu Primary Health Center Semarang.This research was pre-experiment method, using one group pre and post-test design. Sampel for this research were 38 participants, aged 15-44 years old. Data was analyzed by paired sample T-test and wilcoxon test.Result showed the difference between blood sugar level before and after first until fourth zumba (p-value 0,0001 < Î± 0,05), so there was effect of zumba excercise with blood sugar level since blood sugar level decrease significantly in the four time of zumba exercises.Zumba as one of alternative solutionÂ  to control blood sugar level, so diabetes mellitus patient was recommended to practice it.Keywords :diabetes mellitus, gymnastic zumba, blood sugar level